Analisis Yuridis Pertanggungjawaban Pidana terhadap Pelaku Penangkapan Ikan dengan Bahan Berbahaya Beracun : (Studi Putusan: Nomor: 239/Pid.Sus/2020/PN Kpg) - Oktovianus Kelfin Tully; Jimmy Pello; Bhisa V. Wilhelmus (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
Fishing using toxic hazardous materials is a criminal offense of "illegal fishing", which violates the provisions of Law Number 45 of 2009 concerning Amendments to Law Number 31 of 2004 concerning Fisheries. This was also carried out by the Defendant with the initials JLLF based on the Decision of the Kupang District Court Class 1A with case number: 239/Pid.Sus/2020/PN Kpg. This research is a normative juridical research, so the data sources used are primary data sources, secondary data, and tertiary data. Primary data is obtained from several legal rules such as the Criminal Code (Criminal Code), Law Number 45 of 2009 concerning Fisheries and Court Decisions, secondary data is obtained from libraries, journals, and the internet, and tertiary data is obtained from dictionaries, wikipedia, and encyclopedias. The data were analyzed in a descriptive-qualitative manner. The results of this study show that (1) Criminal liability for fishing perpetrators using toxic hazardous materials in Article 84 paragraph (1) of Law of the Republic of Indonesia Number 45 of 2009 concerning Amendments to Law of the Republic of Indonesia Number 31 of 2004 concerning Fisheries is in accordance with the elements contained in the formulation of the article. (2) Basis for Judge's Consideration in the Request for Criminal Liability for the Crime of Fishing with Toxic Hazardous Materials in Decision Number: 239/Pid.Sus/2020/PN Kpg. Judging from the elements contained in the articles of indictment as well as aggravating and mitigating matters.